Musica Antiqua-Musica Nova? : three unpublished inventories from Tongeren and Hasselt, in the context of religious music in the Southern Netherlands and the Prince-bishopric of Liège (c. 1650–1790) - Eugeen Schreurs (Musicologica Brunensia, 2018)
In the Catholic Southern Netherlands and the Prince-bishopric of Liège a lot of music from c. 1650–1790, as well as contextual archival information, is lost because of changes in fashion, wars and negligence. This is particularly regrettable since it caused some underestimated gaps in our music history. Among other things, often interesting, local composers remain unnoticed. So we are missing a lot of information about the music itself, circulation of music, music prices, performance practices. Sources that can certainly help in reducing this gap are the more than 40 historical music inventories. No doubt more inventories will be found, but the current knowledge is representative enough to draw some conclusions concerning the music history of the Catholic Low Countries and its place in Europe. It is quite clear that especially the Italian style had an enormous influence, also on local composers.